Morphological analysis of peritoneal fluid in fumarate hydratase deficiency-associated renal cell carcinoma: a case report - Du, Yingying; Shang, Yu; Shi, Chang (Frontiers in Oncology, 2025)
Fumarate hydratase deficiency-associated renal cell carcinoma (FH-RCC) is a rare, aggressive subtype of renal cell carcinoma (RCC) driven by FH gene mutations. Its non-specific imaging features and heterogeneous pathological morphology complicate early diagnosis. This case report describes the cytological evaluation of peritoneal fluid from a 35-year-old male with FH-RCC, highlighting distinct cellular features within the effusion. These findings provide insights into the clinicopathological differential diagnosis of serous cavity effusions, potentially enhancing the recognition and management of this uncommon malignancy.